Study of the Levels of Trace and Ultra-Trace Element Profile in Patients with Acute Myocardial Infarction in Babylon Province - Ahmed F. F. Al-Baaj; Abbas O. Hussein; Samar H. Shammar; Mufeed J. Ewadh (Medical Journal of Babylon, 2025)
Background: Acute myocardial infarction (AMI) is considered one of the most threatening cardiovascular diseases, also called a heart attack, which occurs when there is a blockage in the blood flow to the heart muscle. Objectives: The aim of this study was to investigate the levels of trace and ultra-trace element profiles in patients with acute myocardial infarction. Materials and Methods: This study involved 100 patients with AMI. The study also included a control group (CG) of 100 participants. The period of the study extended from August 2022 to August 2023. The study was conducted within Iraq, specifically at the Department of Biochemistry within the College of Medicine, University of Babylon, and at Shaheed al-Muhrab Center situated in Marjan Teaching Hospital within Hilla City, Iraq. Determination of trace and ultra-trace elements was done by using a fully automated Shimadzu AA-7000 series of atomic absorption spectrophotometers. Results: Results indicate higher levels of some elements, copper, iron, and nickel, in the AMI group, and lower levels of other elements, such as zinc and selenium, in the patient group when compared to the control group. Conclusion: Abnormal levels of trace elements like zinc, copper, iron, selenium, and nickel have been observed in myocardial infarction patients. These imbalances may contribute to oxidative stress, inflammation, and altered metabolic processes, potentially influencing the development and progression of heart attacks. Further research is needed to clarify their specific roles and therapeutic implications.